The Development of a Supervision System for FSKTM Undergraduate Students - Chong Er Juan; Norfaradilla Wahid (Applied Information Technology And Computer Science, 2021)
FSKTM Supervision System is a web-based system and it is developed especially for Faculty of Computer Science and Information Technology (FSKTM) year 3 students. This project is proposed to assist year 3 student when they are starting and doing their final year project. Student will be more easily and systematically to do appointment to approach to their potential lecturer to discuss about their final year project and get notification for the notice announced. Coordinator can easily gather all the year 3 students and upload important information without anyone left out. This project is developed based on Prototyping method where improvement is done from time to time. The development tool that used to build supervision system are Brackets, Notepad and XAMPP. Additionally, phpMyAdmin is used for system database. Based on the testing by test plan, it is shown that the actual output is same as the expected output. For the user acceptance testing, most of the respondents felt strongly satisfied and satisfied with the system.